Levetiracetam versus Phenobarbitone in Neonatal Seizures - An Open label Randomized Controlled Trial - Nikhil D Kulkarni; Suman Rao P N; B Lakshmi Parvathi; Swarnarekha Bhat (RGUHS Journal of Nursing Sciences)
BackgroundnbspPhenobarbitone is the traditional first-line anticonvulsant for neonatal seizures while levetiracetam a newer anti-epileptic has uncertain efficacy in comparisonObjectivenbspTo evaluate the efficacy and safety of levetiracetam versus phenobarbitone in term and preterm infants with clinically apparent seizures in a tertiary care neonatal setting guiding safer more effective neonatal seizure managementMethodsnbspThis study aimed to compare the efficacy and safety of levetiracetam 30 mgkgdose and phenobarbitone 20 mgkgdose in controlling neonatal seizures. An open-label parallel randomized controlled trial RCT was conducted in a neonatal intensive care unit NICU in IndiaResultsnbspSeizure cessation rates were 70 in the levetiracetam group and 66.6 in the phenobarbitone group with no statistically significant difference P 0.83.ConclusionnbspLevetiracetam and phenobarbitone demonstrated comparable efficacy and safety in managing neonatal seizures. Levetiracetam could be considered a viable alternative to phenobarbitone as a first-line treatment. Further studies are needed to confirm these findings especially regarding levetiracetams side effect profile.